2013
DOI: 10.1111/ijd.12116
|View full text |Cite
|
Sign up to set email alerts
|

AIDS‐related Kaposi's sarcoma in Brazil: trends and geopolitical distribution

Abstract: Prevalence of KS declined after the introduction of ART in all regions of Brazil, suggesting individual protection conveyed by ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…10,11 In a study published by Saraceni et al in 2013, the prevalence of KS decreased after the introduction of ART in all regions of Brazil, suggesting an individual protection of the antiretroviral medication. 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 In a study published by Saraceni et al in 2013, the prevalence of KS decreased after the introduction of ART in all regions of Brazil, suggesting an individual protection of the antiretroviral medication. 12 …”
Section: Discussionmentioning
confidence: 99%
“…12 This is probably due to the high frequency of human herpes virus type 8 (HHV 8) infection, also called KS-associated herpes virus (KSHV) in men who have sex with men (MSM), a group predominantly affected by HIV infection in Brazil and in the state of Pernambuco. 13-15 Mean age was 33 years, with 32% of the patients being under 25 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review of clinical records in a teaching hospital in North-western Nigeria covering the period 1994–2004 also found the prevalence of Kaposis sarcoma to be very low (only 27cases in 11 years) [53]. Another study that examined trends of Kaposis sarcoma for the period 1982–2009 in Brazil found a prevalence of only 2.4 % among HIV+ individuals [54]. The study also showed a significant reduction in Kaposis sarcoma prevalence attributed to increased access to HAART over time [54].…”
Section: Discussionmentioning
confidence: 99%
“…Another study that examined trends of Kaposis sarcoma for the period 1982–2009 in Brazil found a prevalence of only 2.4 % among HIV+ individuals [54]. The study also showed a significant reduction in Kaposis sarcoma prevalence attributed to increased access to HAART over time [54]. Another study that evaluated time trends of AIDS-defining diseases diagnosed in Italy during the pre-HAART period (1982–1996) noted downward trends for mycoses, PCP, Karposis sarcoma and non-Hodgkin’s lymphomas and upward trends for mycobacterioses, bacterial and protozoal infections [55].…”
Section: Discussionmentioning
confidence: 99%